Designing a sequential Ugi/Ullmann type reaction for the synthesis of indolo(1,2-a)quinoxalinones catalyzed by CuI/l-proline - Balalaie, Saeed; Bararjanian, Morteza; Hosseinzadeh, Saeedeh; Rominger, Frank; Bijanzadeh, Hamid Reza; Wolf, Eckardt (Tetrahedron, 2011)
An efficient strategy for the one-pot syntheses of indolo[1,2-a]quinoxalinones catalyzed by CuI have been developed. The procedures combine the Ugi four-component reaction of aldehydes, 2-iodoaniline, 2-indole carboxylic acid, and isocyanides followed by the copper-catalyzed intramolecular N-arylation of the Ugi product in one-pot procedure, which afford the desired products in good to very good yields.